Soft Power Architecture: (Un)intentional and Incidental in Culture Relations Policies - Filipović, Ivan; Vasiljević Tomić, Dragana (Arhitektura i urbanizam, 2019)
States' cultural policies for international relations take various forms, both intangible and tangible. This paper will focus on the latter, namely, exported architectural manifestation utilized as cultural negotiation tools. Architecture is viewed and examined as a cultural resource, subsequently having the power to influence bilateral relations Presenting a new term, ‘soft power architecture’ as conceived, exported, and state-controlled spatial manifestation, with a clear set of goals inscribed within cultural relations policies. These typologies have a profound impact and yet the policy makers remain unbothered by the importance of the said cultural resources. Requirements of the re-conceptualization of the state's policies regarding the planning, implementation and management processes for diplomatic-consular outpost will be discussed. Lastly, the case study of the new Japanese embassy in Belgrade, Serbia, will be examined, noting particularities of its processes, arguing an unintentional paradigmatic shift, providing a theoretical and methodological framework for future research.